Educational Financing Management: Analysis of Sources and Use of Educational Budgets in Elementary Schools - Gunadi, Gugun; Suherman, Irman; Napisah, Siti Alpi; Fauziah, Namira; Novianti, Annisa (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The importance of financing in education brings school principals to try to manage the available budget properly. Significant to improve the quality of education. This study aims to determine the management pattern of education costs in elementary schools in Bogor. This research method is a case study. Data was collected through interviews and documents on primary school financing. Data analysis using the Miles & Huberman model includes (1) data reduction, (2) data display, and (3) concluding. The results of the study illustrate that as much as 70% of the source of income for elementary schools in Bogor comes from the government, namely in the form of BOS funds, while the remaining 30% comes from tuition fees and foundation funds for private elementary schools. The Education Budget pays salaries and procures infrastructure, office stationery, student activities, and school operations. The results of this study indicate that there is still a lack of attention from schools to developing the quality of human resources, which is indicated by the absence of an allocation of education funds that leads to the competence of teachers, staff, and students.